The effects of topical anesthesia on outcomes and glucose control in diabetic patients treated with split-thickness skin graft surgery. Issue 3 (17th December 2022) - Chang, Dun-Hao; Lin, Shen-Che; Lin, Yi-Ting; Chang, Ke-Chung; Chan, Chien-Lung
Abstract : Background: Using split-thickness skin grafting to treat diabetic foot and leg ulcers is common. Diabetic patients usually exhibit multiple comorbidities and high risks of adverse responses to general and spinal anesthesia. Topical anesthesia can be an alternative to avoid these risks. In this study, the clinical experience of split-thickness skin grafting under topical anesthesia was demonstrated, to evaluate its effectiveness and benefits in diabetic patients. Methods: From 2018 to 2020, diabetic patients with foot or leg wounds undergoing split-thickness skin grafting were reviewed and categorized into two groups according to the anesthesia methods: topical anesthesia and general/spinal anesthesia. Patient demographics, wound characteristics and healing status, postoperative complications, and perioperative blood glucose levels were recorded and analyzed. Results: During the study period, 28 patients underwent split-thickness skin grafting under topical anesthesia and 46 under general/spinal anesthesia. The rate of complete wound healing in 4 weeks was similar in both the groups. The topical anesthesia group suffered fewer postoperative infections (3.6% vs 21.7%, p = 0.044), required shorter postoperative hospitalization (8.3 ± 6.2 vs 11.1 ± 7.2 days, p = 0.048), and exhibited lower mean blood glucose levels and less glucose variability than the general/spinal anesthesia group. Conclusion: Conducting split-thickness skin grafting under topical anesthesia was shown to be a safe and effective means of treating leg and foot wounds in diabetic patients.